Effect of ultra violet irradiation on life table of Mediterranean flour moth, Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) - Ali Mirshekar (Azarian Journal of Agriculture, 2020)
Three age groups of eggs of the stored grain pests, Ephestia kuehniella (1, 2, and 3days old) were exposed to ultraviolet irradiation with 254 nm wavelength (UV-C) for different exposure times (0.5- 40 min.) under controlled conditions to determine irradiation effect on egg-hatching. The effect of UVC-irradiation on reproduction and population growth parameters was investigated for eggs irradiated for 0.5, 1 and 1.5 minutes. An increase in time of exposure to irradiation caused a gradual decrease in percentage of hatching off eggs in all age groups of eggs. In all treatments, the older eggs were more sensitive to UV-rays than younger ones. The results indicated that different exposure periods of UV-irradiation could affect the reproduction and population growth parameters. The highest value of net fertility rates was observed in 1, 2, and 3-days-old eggs which were treated with 0.5 min exposure time (26.69 ± 4.66, 5.99 ± 0.57 and 1.55 ± 0.16 eggs/female, respectively). Both the intrinsic rate of increase (rm) and the net reproductive rate (R0) decreased with increasing the exposure time from 0.5 to 1.5 min while the mean generation time (Tc) and doubling time (DT) increased within this irradiation range. The lowest amount of rm was determined in 1, and 2 days-old eggs at 1.5 min and in 3-day-old eggs at 1 min exposure times (0.037 ± 0.0025, 0.004 ± 0.0016 and 0.006 ± 0.0008 day-1, respectively). UVC-irradiation may be used as an alternative approach to control of stored product pests.